How do you evaluate 2 e^( ( 3 pi)/8 i) - 3e^( ( 7 pi)/8 i)2e3π8i3e7π8i using trigonometric functions?

1 Answer
Jun 7, 2018

:2 e^((3 pi)/8 i)- 3 e^((7 pi)/8 i)~~( 3.54+0.70 i):2e3π8i3e7π8i(3.54+0.70i)

Explanation:

2 e^((3 pi)/8 i)- 3 e^((7 pi)/8 i)2e3π8i3e7π8i

We know e^(i theta) = cos theta +i sin thetaeiθ=cosθ+isinθ

(3 pi)/8 ~~ 1.178097 , (7 pi)/8 ~~ 2.7488933π81.178097,7π82.748893

:. 2 e^((3 pi)/8i) = 2(cos ((3 pi)/8)+ i sin ((7 pi)/8))

=0.765367+ 1.847759 i

:. 3 e^((7 pi)/8 i) = 3(cos ((7 pi)/8)+ i sin ((7 pi)/8))

~~ -2.77164 + 1.14805 i

:.2 e^((3 pi)/8 i)- 3 e^((7 pi)/8 i)

~~(0.765367+ 1.847759 i)- ( -2.77164 + 1.14805 i)

~~( 3.54+0.70 i) (2 dp) [Ans]